"Ropivacaine With or Without Dexamethasone for Ultrasound-Guided Pericapsular Nerve Group Block in Hip Surgery: A Comparative Study" - Dr. Sravani M; Dr. Sahana S; Dr. Kiran Kumar O (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: The pericapsular nerve group (PENG) block is a novel, ultrasound-guided regional anaesthesia technique targeting the articular branches of the femoral, obturator, and accessory obturator nerves. It has demonstrated efficacy in providing analgesia for hip surgeries while preserving motor function. Adjuvants such as dexamethasone have been explored to prolong analgesic duration and improve outcomes when combined with local anaesthetics. Aim of this study is to compare the efficacy and duration of analgesia of ultrasound-guided PENG block using 0.5% Ropivacaine alone versus 0.5% Ropivacaine with Dexamethasone in patients undergoing hip surgery. Methods: A prospective, randomized, double-blind clinical study was conducted on 60 patients aged 18 to 65 years belonging to ASA I–II scheduled for elective hip surgery between June 2023 and May 2024 in the Department of Anaesthesiology at Sri Balaji Medical College and Hospital, Tirupati. Patients were randomly divided into two groups (n=30 each): Group A: Received 20 ml of 0.5% Ropivacaine. Group B: Received 20 ml of 0.5% Ropivacaine + 8 mg Dexamethasone. The PENG block was performed under ultrasound guidance preoperatively. Patients were monitored for 24 hours postoperatively for visual analogue scale (VAS) pain scores, duration of analgesia (time to first rescue analgesic), total analgesic consumption, motor function, and any complications. Results: The duration of analgesia was significantly longer in Group B (mean: 18.2 ± 2.4 hours) compared to Group A (mean: 11.6 ± 1.8 hours, p < 0.001). VAS scores at 6, 12, and 18 hours postoperatively were significantly lower in Group B (p < 0.05). Total rescue analgesic consumption was reduced in the dexamethasone group. No significant motor blockade or adverse effects were observed in either group. Conclusion: The addition of dexamethasone to ropivacaine in ultrasound-guided PENG block significantly prolongs the duration of analgesia and reduces postoperative pain and analgesic requirements without increasing adverse effects. This combination may enhance perioperative pain management in hip surgeries.